The β-barrel membrane protein insertase machinery from Gram-negative bacteria - Noinaj, Nicholas (Curr Opin Struct Biol, 2015)
The outer membranes (OM) of Gram-negative bacteria contain a host of β-barrel outer membrane proteins (OMPs) which serve many functions for cell survival and virulence. The biogenesis of these OMPs is mediated by the β-barrel assembly machinery (BAM) complex which is composed of five components including the essential core component called BamA that mediates the insertase function within the OM. The crystal structure of BamA has recently been reported from three different species, including a full-length structure from Neisseria gonorrhoeae. Mutagenesis and functional studies identified several conformational changes within BamA that are required for function, providing a significant advancement towards unraveling exactly how BamA and the BAM complex are able to fold and insert new OMPs in the OM.